Peran Aksiologi Sains terhadap Kehidupan Sehari-hari - Dynda Prista; Muhammad Nashirul Haq; Agung Winarno (Jurnal bintang manajemen, 2025)
Science axiom is a branch of philosophy that discusses ethical, aesthetic, and moral values in science, as well as their role in human life. This research aims to examine the role of science axioms in daily life, especially in directing the wise and responsible use of science. This study uses the Systematic Literature Review (SLR) method to analyze literature related to the role of science axioms in education, technology, health, and environmental aspects. The results of the study show that science axioms not only function as an ethical framework in technological and scientific innovation, but also serve as a guide in decision-making based on moral values. In education, the axioms of science help instill a critical and ethical mindset; in the field of technology, it sets limits in the use of new innovations; In the health sector, axiology is a guideline in ethical medical decision-making, while in environmental contexts, it promotes sustainability and intergenerational justice. Thus, the axiom of science ensures that the development of science is always directed towards human welfare and environmental sustainability.